Analysis of Cadmium (Cd) and Lead (Pb) Heavy Metal Content in Shell and Mangroves at Bima Bay - Khairuddin Khairuddin; M Yamin (Journal of Science and Science Education, 2021)
This study aims to determine the levels of heavy metals (Cd) and (Pb) in shellfishes and mangroves at Bima bay. The results showed that bivalves and mangrove tissue were analyzed for heavy metal content in the form of lead (Pb), and Cadmium (Cd) using an Atomic Absorption Spectrophotometer.  From tissue analysis, it indicates that the content of heavy metals lead (Pb) in 3 species of Shellfish which showed different results; Blood shells (Anadaragranosa) of 0.756 ppm, Hiatula shells (Hiatula chinensis) 1.59 ppm, and Shells (Siliqua winteriana) 1.171 ppm. Cadmium (Cd) metals in Shells are each found; Cockle shell (Anadara granosa) of 0.802 ppm, Hiatula shells (Hiatula chinensis) 0.334 ppm and Shells (Siliqua winteriana) 0.066 ppm. The content of lead metal (Pb) in the tissue of small mangrove leaves (Ryzophora apiculata) is 3.21 ppm and the mangrove leaves (Sonnerati aalba) is 3.74 ppm. For Cd levels in small mangrove leaves (Ryzophora apiculata) is 0.41 ppm while in mangrove leaves (Sonneratia alba) is 0.24 ppm